Establishing the minimally important clinical difference for the oral health impact profile in Malaysians provided with removable partial dentures / Siti Fauzza Ahmad - Siti Fauzza, Ahmad (2021)
Future demand for a removable partial denture (RPD) remains as more adults retain their natural teeth into old age. Partial tooth loss often leads to masticatory function disturbances and negatively affects the quality of life (QoL). Prosthodontic rehabilitation with RPD improves QoL; however, the statistically significant change with many Oral Health-Related Quality of Life (OHRQOL) instruments, may not be clinically meaningful. The Malaysian version of Oral Health Impact Profile, OHIP(M)-45 questionnaires has been validated and adapted; however, its clinical interpretability has not been established. The smallest change in OHRQoL score perceived by a patient as beneficial, following an intervention, is termed Minimal Important Difference (MID). There are two methods to estimate the MID estimation; i) distribution-based approach which compares changes in OHRQoL scores after intervention through statistical parameters, ii) anchor-based approach which correlates the change with clinical measures. This pre-post intervention study investigated the change in OHRQoL, partially dentate subjects after RPD therapy and determined the MID for OHIP(M)45, using both approaches. The association between subjective perception and clinical outcomes (bite force and masticatory performance) were also determined. Subjects completed OHIP(M)-45 questionnaires before and after the intervention. The OHIP(M)-45 score ranges from 0-180 with a lower score indicating better OHRQoL. The clinical anchors, Global Transitional Scale (GTS) questionnaire, bite force and masticatory performance were used. Bite force was measured using a digital dynamometer while masticatory performance using gravimetric sieving method, (mesh sizes ranging from 4.00mm to 0.425mm) with alginate pellet as a test food. Statistical analysis was performed using iv Paired t-test, Wilcoxon Signed Rank and Friedmann test for within and between comparison while the relationship between subjective and objective measurements using Linear Regression and Spearman Rho. A total of 118 subjects enrolled with mean age 58.3 (SD±10.4) years, number of teeth 16.0 (SD±6.6) and number of occluding pairs 4.8 (SD±3.8). A significant reduction of 40% in the prevalence of impact (p<0.001) was observed with RPD therapy. The mean OHIP(M)-45 change score was 17.36 (95%CI (13.53;21.20, ES=0.76, p<0.001) with high treatment effect in the domains of physical pain (ES=0.78) and psychological discomfort (0.82) and low effect in social disability domain (ES=0.30). The GTS measure showed that 13%-24% of subjects perceived a little improvement in their QoL, mainly in chewing with a significant association (p<0.05). The estimated MID was 11. A significant increase in bite force (p<0.05) and improvement in masticatory performance (p<0.05) with the new dentures were observed, and a significant association was found between them. However, they showed no significant association with the change in OHIP(M)-45 scores. MID estimates using bite force and masticatory performance as anchors were 19 and 21 OHIP units respectively. In conclusion, RPD therapy improved subjects' OHRQoL, bite force and masticatory performance. The OHIP(M)-45 instrument is found to be responsive and sensitive to change, and the MID for OHIP(M)-45 for RPD therapy is established. Keywords: OHRQoL, MID, removable partial denture, bite force, masticatory performance